Liver pathology - Xiao, Shu-Yuan; Oshima, Kiyoko (Demos surgical pathology guides., 2015)
Liver Pathology covers the key entities and diagnoses that pathologists see in daily practice, focusing on the salient H & E histopathology of each entity with concise descriptions of clinical features, differential diagnosis, and references for further study. It provides the opportunity for correlation with clinical data and radiologic and laboratory findings that are essential to correct diagnosis of non-neoplastic disease and correlation with morphologic and immunohistochemical features in the case of neoplastic liver disease. The book presents information in a bulleted format with H & E illust.